The disease as sign and the symbolic forms of the sick body on the horizon of comprehension d the dermatology nineteenth - Cardona-Rodas, Hilderman (Saúde e Sociedade, 2020)
The clinical dermatology of the nineteenth century bases and displays a thought by similarity in an aesthetic representation of what can be understood as disease. Thus, the pathological surfaces provide a material of reflection and appropriation of the sick body where body, language and event converge to give meaning to the alterations that converge in the pathological state. This text reflects on these symbolic forms of naming the disease that occur in descriptions, clinical observations, treaties of dermatology, Atlas of pathological anatomy or iconographic albums of the nineteenth century, where it is possible to see a regime of visualization of the pathological that reveals itself in the medical perception of the lesion and its location. The analysis of skin diseases that disfigure the face from some clinical and iconographic records from the end of the 19th century puts into play a link between image and word in terms of dermatological efficacy in ways of capturing the experience of the disease, which has the sick body as a theater of performative sensitivity.